2019
DOI: 10.1002/anie.201904288
|View full text |Cite
|
Sign up to set email alerts
|

meta‐Selective C−H Activation of Arenes at Room Temperature Using Visible Light: Dual‐Function Ruthenium Catalysis

Abstract: Ruthenium-catalyzed meta-C À Ha ctivation of arenes at room temperature is reported to proceed under blue-light irradiation. Avariety of heteroarenes are compatible with this photochemical process,w hich leads to the corresponding meta CÀCc oupling products in good to very good yields.I nitial mechanistic studies suggest as ingle-electron transfer process occurs between ap hotoexcited Ru II -cyclometalated complex and alkylh alides,e nabling meta-C À H functionalization reaction via carbon-centered radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(66 citation statements)
references
References 46 publications
3
59
0
4
Order By: Relevance
“…Visible‐light photoredox catalysis allowed for direct transformations at ambient temperature, however, additional iridium or ruthenium photocatalysts were required in these transformations among others as reported by MacMillan, Molander and Doyle. In contrast, Ackermann and Greaney recently disclosed photo‐induced ruthenium‐catalyzed remote C−H alkylations. After submission of the present manuscript, Greaney has reported on a ruthenium‐catalyzed arylation of phenylpyridines using visible light, which was proposed to occur by an oxidative addition/reductive elimination process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visible‐light photoredox catalysis allowed for direct transformations at ambient temperature, however, additional iridium or ruthenium photocatalysts were required in these transformations among others as reported by MacMillan, Molander and Doyle. In contrast, Ackermann and Greaney recently disclosed photo‐induced ruthenium‐catalyzed remote C−H alkylations. After submission of the present manuscript, Greaney has reported on a ruthenium‐catalyzed arylation of phenylpyridines using visible light, which was proposed to occur by an oxidative addition/reductive elimination process .…”
Section: Introductionmentioning
confidence: 99%
“…Greaney [15] recently disclosed photo-induced ruthenium-catalyzed remote C À Ha lkylations.A fter submission of the present manuscript, Greaney has reported on ar utheniumcatalyzed arylation of phenylpyridines using visible light, which was proposed to occur by an oxidative addition/ reductive elimination process. [16] Within our program on sustainable CÀHa ctivation, [17] we have now devised the first light-driven ruthenium-catalyzed CÀHa rylations at ambient temperature (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Grasping the essence of the mechanism of these systems one can intuitively conclude that the unique feature of photoredox catalysis is not the ability to facilitate any specific reaction but rather its capability to turn inactive substrates into reactive radical intermediates through high-energy intermolecular outer-sphere electron transfer. Consequently, the most typical application of TMPRCs includes the generation of, among many others, electrophilic α-carbonyl radicals [29], trifluoromethyl radicals [30], arene radical cations, iminium ions, and enone radical anions [31], of which these intermediates have been used to drive other types of transformations including atom transfer radical additions [32], arene C−H functionalizations [25,33,34], and amine α-functionalizations to [2 + 2] cycloadditions [35,36]. Cooperative catalysis, in which another transition metal co-catalyst is sensitized through electron transfer and its catalytic cycle is supported by the photoredox catalyst has been recently added to the arsenal of applications [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering work in this extremely challenging research field was reported concomitantly by the groups of Ackermann [100] and Greaney [101], and concerned unique Ru-catalyzed meta-selective C-H alkylation of arenes. The ruthenium-catalyzed meta-selective C-H functionalization through arene σ-activation was already well established yet limited by harsh reaction conditions and elevated reaction temperatures.…”
Section: Direct Metalation and Visible-light Absorption By A Single Cmentioning
confidence: 99%